Genosida Kebudayaan dalam Novel Ṡulāṡiyyat Garnāṭah Karya Radwa ‘Asyur (Analisis Sosiologi Sastra) - Siti Munifah Wardah; Yoyo Yoyo (Institut Agama Islam Negeri Metro, 2022)
This study aims to describe the forms of cultural genocide and the impacts that occur as a result of cultural genocide in the novel Ṡulāṡiyyat Garnāṭah by Radwa ‘Asyur. The study uses literary sociology of literature to reveal the correlation between the text and the context. The method used in this research is descriptive qualitative method. This study uses two data sources, namely primary data sources and secondary data sources. Primary data sources are in the form of narrative texts and conversations contained in the novel Ṡulāṡiyyat Garnāṭah, while secondary data sources are obtained from various literary sources in the form of books, journal articles, and theses. The data collection method used in the form of library research. The results of this study indicate that in the novel Ṡulāṡiyyat Garnāṭah there are 5 (five) forms of cultural genocide committed by Christians against Muslims, namely Christianization, destruction of Arabic manuscripts, prohibition of Islamic symbols, intimidation of Muslims, and deportation. Then there are 2 (two) impacts of cultural genocide, namely pretending to leave Islam and rebellion.